Soaring world cereal prices. A boon for African farmers? - (:unkn) unknown (My University, 2011)
The soaring world cereal prices in 2007/2008 and the subsequent riots in several sub-Saharan African cities reignited the debate on food security policy. Could rising world cereal prices actually be a blessing in terms of boosting food production by guaranteeing more attractive prices for farmers? This implies determining whether global price fluctuations are actually transmitted to national market prices. This was the objective of a study focusing on five countries in the region. Between 1994 and 2009, the degree of transmission of world rice prices to domestic markets varied considerably from one country to another: low or even inexistent in Mali, Cameroon and Madagascar; high in Senegal and Niger. The 2007/2008 price increases made no structural changes to the types of transmission identified over the long term. The segmentation of food markets between imported rice, local rice and other foodstuffs explains this imperfect transmission of global prices to sub-Saharan markets. This finding must be taken into consideration in food security strategies in sub-Saharan Africa.
Keywords: African Research